Discussion of the Legal Responsibilities of Anesthesiology Technicians with Representative Cases - Gündoğmuş, Ümit Naci (The Bulletin of Legal Medicine, 2001)
For various reasons, anesthesia procedures are often performed by anesthesia nurses or technicians in Turkey. It seems that technicans’ performing such procedures is considered to be normal even in situations where an anesthesiology specialist is present, and neither specialists nor the technicians do not seem to be aware of their responsibilities. In this study, we aimed to argue the situation, based on the cases selected from our country. Key words: Anesthesia technicians, responsibility, medical malpractice